Characteristics associated with elevated 1‐h plasma glucose levels during a 75‐g oral glucose tolerance test in non‐obese Japanese men - Motonori Sato; Yoshifumi Tamura; Yuki Someya; Kageumi Takeno; Hideyoshi Kaga; Satoshi Kadowaki; Daisuke Sugimoto; Saori Kakehi; Takashi Funayama; Yasuhiko Furukawa; Ruriko Suzuki; Takashi Nakagata; et al. (Journal of Diabetes Investigation, 2020)
Abstract Elevated 1‐h plasma glucose (1h‐PG; ≥155 mg/dL) during an oral glucose tolerance test is a risk factor for type 2 diabetes. However, the metabolic characteristics of non‐obese Asians with elevated 1h‐PG are unknown. Thus, we studied 59 non‐obese Japanese men with normal glucose tolerance. We divided study participants into the Low 1h‐PG group (<155 mg/dL) and the High 1h‐PG group (≥155 mg/dL). We compared the metabolic characteristics of the groups, including tissue‐specific insulin sensitivity measured using a two‐step hyperinsulinemic‐euglycemic clamp. Insulinogenic index and adiponectin levels were significantly lower in the High 1h‐PG group than in the Low 1h‐PG group. Other characteristics, including insulin sensitivity, adiposity and ectopic fat accumulation, were similar between the groups. In conclusion, non‐obese Japanese men with high 1h‐PG have impaired early‐phase insulin secretion and lower adiponectin levels. Insulin resistance and abnormal fat distribution were not evident in this population.